Examining the Link Between Perceptions of Relationship Quality With Parole Officers and Recidivism Among Female Youth Parolees. (January 2015) - Vidal, Sarah; Oudekerk, Barbara A.; Reppucci, N. Dickon; Woolard, Jennifer
This study explored 140 female youth parolees' characterization of their relationships with their parole officers (PO), examined whether the quality of PO–youth relationships relate to recidivism, and explored the role of parental assistance in acquiring services during reintegration as a moderator of the link between PO–youth relationship and recidivism. Female youth perceived both an interpersonal and professionalism aspect of PO–youth relationship. The association between the interpersonal quality of PO–youth relationship and violent recidivism was strong and significant for those who had low parental assistance, but nonsignificant for those with high parental assistance. Implications for research, policy, and practice are discussed.